2019
DOI: 10.1007/s10811-019-01858-x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic co-digestion of olive mill solid waste and microalga Scenedesmus quadricauda: effect of different carbon to nitrogen ratios on process performance and kinetics

Abstract: Anaerobic digestion (AD) is one of the most efficient processes for treating agri-food waste in order to obtain renewable energy. Olive mill solid waste (OMSW) is the main residue from the two-phase olive oil manufacturing process; it has a high organic content and high C/N ratio, which hinders its AD, giving low methane yield. In the present study, a microalga, Scenedesmus quadricauda (S. quadricauda), was used as co-substrate for the AD of OMSW to compensate for its nitrogen deficiency. The robustness and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
(51 reference statements)
3
17
0
Order By: Relevance
“…They reported a 75% of biodegradability of Laminaria digitata during anaerobic assays. Fernández-Rodríguez et al (2019b) also found an OMSW biodegradability of 56%, very similar to that obtained in this experiment. In addition, the mentioned study also found an improvement in the biodegradability of different microalgae-OMSW mixtures compared with those obtained for the substrates separately.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They reported a 75% of biodegradability of Laminaria digitata during anaerobic assays. Fernández-Rodríguez et al (2019b) also found an OMSW biodegradability of 56%, very similar to that obtained in this experiment. In addition, the mentioned study also found an improvement in the biodegradability of different microalgae-OMSW mixtures compared with those obtained for the substrates separately.…”
Section: Discussionsupporting
confidence: 88%
“…The mesophilic batch experiments (BMP tests) were performed with an inoculum to substrate ratio fixed at 2 (as volatile solid (VS)) as described elsewhere (Fernández-Rodríguez et al 2019a). A 10% micronutrient solution (Fernández-Rodríguez et al 2019b) and nitrogen gas was added at the beginning of the experiment in order to keep anaerobic conditions. The anaerobic reactors of 250 mL total volume were placed in a thermostatic water bath at a controlled temperature of 35 ± 2 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The methane yield obtained during AD of 100% OMSW was 341 ± 22 mL CH 4 /g VS added. This value of methane yield obtained for the BMP test of OMSW was in accordance with previous studies[3,41,58]. After 30 days of experiment, the maximum methane yield obtained was 383 ± 2 mL CH 4 /g VS added for A1 pre-treatment.…”
supporting
confidence: 91%
“…The adjustment of the C:N ratio to 30 using ammonium, increased the CH 4 production and reduced the lag phase of anaerobic digestion of swine manure (Wijesinghe et al, 2019). Fernández-Rodríguez et al (2019) observed the highest methane yield in the anaerobic co-digestion of olive mill solid waste and microalga Scenedesmus quadricauda when C:N ratio was adjusted to 31.9 using the microalga as a nitrogen source. However, none of the existing studies discusses the possible inhibiting effects of the added compounds.…”
Section: Challenges and Future Perspectives (Opportunities And Research Needs)mentioning
confidence: 94%